Multivariate Sobel–Uppuluri–Galambos-Type Bounds - Chen, John T.; Seneta E. М. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We improve the known upper and lower bounds for the probability of the fact that exactly k ievents should occur in a group consisting of n ievents simultaneously for all i= 1, 2, ..., d.